Community ecology processes, models, and applications - Verhoef, Herman A.; Morin, Peter Jay, 1953- (Oxford : Oxford University Press, 2010)
This is an up-to-date study of patterns and processes involving two or more species. The book strikes a balance between plant and animal species and among studies of marine, freshwater and terrestrial communities.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Biotic communities